Rosuvastatin inhibits interleukin (IL)-8 and IL-6 production in human coronary artery endothelial cells stimulated with Aggregatibacter actinomycetemcomitans serotype b (2017)
Background:Rosuvastatin exhibits anti-inflammatory effects and reduces periodontal diseases andatherosclerosis; however, its role in regulating periodontopathogen-induced endothelial proinflammatoryresponses remains unclear. The purpose of this study is to determine whether rosuvastatin can reduce theproinflammatory response induced byAggregatibacter actinomycetemcomitans(Aa) in human coronaryartery endothelial cells (HCAECs).Methods:HCAECs were stimulated with purifiedAaserotype b lipopolysaccharide (LPS) (Aa-LPS),heat-killed (HK) bacteria (Aa-HK), or live bacteria. Expression of Toll-like receptors and cellular adhesionmolecules were evaluated by fluorometric enzyme-linked immunosorbent assay. Endothelial cell activationwas evaluated by quantifying nuclear factor (NF)-kappa B-p65 and cytokine expression levels by quan-titative polymerase chain reaction and flow cytometry. Effect of rosuvastatin in expression of the athero-protective factor Kru ̈ppel-like factor 2 (KLF2) and cytokines were also studied using similar approaches.Results:HCAECs showed increased interleukin (IL)-6, IL-8, intercellular adhesion molecule 1, and plateletendothelial cell adhesion molecule 1 expression when stimulated withAa-LPS orAa-HK. NF-kB-p65 activa-tion was induced by all antigens.Aa-induced IL-6 and IL-8 production was inhibited by rosuvastatin, partic-ularly at higher doses. Interestingly, reduced IL-6 and IL-8 levels were observed in HCAECs stimulated withAain the presence of higher concentrations of rosuvastatin. This anti-inflammatory effect correlated witha significant increase of rosuvastatin-inducedKLF2.Conclusions:These results suggestAa-induced proinflammatory endothelial responses are regulatedby rosuvastatin in a mechanism that appears to involveKLF2activation. Use of rosuvastatin to preventcardiovascular disease may reduce risk of endothelial activation by bacterial antigens